Ratio of Circulating IFNγ+ "Th17 Cells" in Memory Th Cells Is Inversely Correlated with the Titer of Anti-CCP Antibodies in Early-Onset Rheumatoid Arthritis Patients Based on Flow Cytometry Methods of the Human Immunology Project. (12th May 2016) - Kotake, Shigeru; Nanke, Yuki; Yago, Toru; Kawamoto, Manabu; Kobashigawa, Tsuyoshi; Yamanaka, Hisashi
Abstract : Rheumatoid arthritis (RA) is a systemic autoimmune disease with chronic joint inflammation characterized by activated T cells. IL-17 and Th17 cells play important roles in the pathogenesis of RA. Recently, plasticity in helper T cells has been demonstrated; Th17 cells can convert to Th1 cells. However, it remains to be elucidated whether this conversion occurs in the early phase of RA. Here, we validated the methods of the Human Immunology Project using only the cell-surface marker through measuring the actual expression of IL-17 and IFN γ . We also evaluated the expression of CD161 in human Th17 cells. We then tried to identify Th17 cells, IL-17 + Th17 cells, and IFN γ + Th17 cells in the peripheral blood of early-onset RA patients using the standardized method of the Human Immunology Project. Our findings validated the method and the expression of CD161. The ratio of IFN γ + Th17 cells in memory T cells was inversely correlated to the titers of anti-CCP antibodies in the early-onset RA patients. These findings suggest that Th17 cells play important roles in the early phase of RA and that anti-IL-17 antibodies should be administered to patients with early phase RA, especially those with high titers of CCP antibodies.